Anesthesia and perioperative challenges for surgical separation of thoraco‐omphalopagus twins: case report - Freitas, Milton Halyson Benevides de (2019)
Background and objectives: Conjoined twins are monozygotic twins physically joined at some part of the body. This is a rare phenomenon, estimated between 1:50,000 to 1:200,000 births. The objective of this report is to present the anesthetic management and the perioperative challenges for a separation surgery. Case report: Thoraco‐omphalopagus twins were diagnosed by ultrasound and were followed by the fetal medicine team of the service. After 11 hours of cesarean surgery, the pediatric surgical team chose to separate the twins. They were monitored with cardioscopy, oximetry, capnography, nasopharyngeal thermometer, urinary output, and noninvasive blood pressure. We chose inhaled induction with oxygen and 4% Sevoflurane. T1 patient was intubated with a 3.5 uncuffed endotracheal tube, and, after three unsuccessful intubation attempts of patient T2, a number 1 laryngeal mask was used. After securing the twins’ airway, the induction was supplemented with fentanyl, propofol, and rocuronium. Mechanical ventilation in controlled pressure mode (6 mL.kg ‐1 ) and lumbar epidural (L1‐L2) with 0.2% ropivacaine (2.5 mg.kg ‐1 ) were used. The pediatric surgical team initiated the separation of the twins via sternotomy, ligation of hepatic vessels. After 2 hours of procedure, the separation was completed, continuing the surgical treatment of T1 and the support of T2 until his death. Conclusions: Conjoined twin separation surgery is a challenge, which requires planning and coordination of a multidisciplinary team during all stages.